A successful crayfish invader is capable of facultative parthenogenesis: a novel reproductive mode in decapod crustaceans - Buřič, Miloš; Hulák, Martin; Kouba, Antonín; Petrusek, Adam; Kozák, Pavel (PLoS One, 2011)
Biological invasions are impacting biota worldwide, and explaining why some taxa tend to become invasive is of major scientific interest. North American crayfish species, particularly of the family Cambaridae, are prominent invaders in freshwaters, defying the "tens rule" which states that only a minority of species introduced to new regions become established, and only a minority of those become invasive and pests. So far, success of cambarid invaders has largely been attributed to rapid maturation, high reproductive output, aggressiveness, and tolerance to pollution. We provide experimental evidence that females of one cambarid species particularly widespread in Europe, the spiny-cheek crayfish Orconectes limosus, are capable of facultative parthenogenesis. Such reproductive mode has never before been recognized in decapods, the most diverse crustacean order. As shown by analysis of seven microsatellite loci, crayfish females kept physically separated from males produced genetically homogeneous offspring identical with maternal individuals; this suggests they reproduced by apomixis, unlike those females which mated with males and had a diverse offspring. Further research is needed to clarify what environmental conditions are necessary for a switch to parthenogenesis in O. limosus, and what role it plays in natural crayfish populations. However, if such reproductive plasticity is present in other cambarid crayfish species, it may contribute to the overwhelming invasive success of this group.
Keywords: Reproduction; partenogeneze; rozmnožování; Female; Animals; Decapoda; Male; Astacoidea; severní raci; ženské pohlaví; Parthenogenesis; Decapoda (Crustacea); zvířata; mužské pohlaví